2009
DOI: 10.1007/s00438-009-0441-y
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and functional validation of a unique set of drought induced genes preferentially expressed in response to gradual water stress in peanut

Abstract: Peanut, found to be relatively drought tolerant crop, has been the choice of study to characterize the genes expressed under gradual water deWcit stress. Nearly 700 genes were identiWed to be enriched in subtractive cDNA library from gradual process of drought stress adaptation. Further, expression of the drought inducible genes related to various signaling components and gene sets involved in protecting cellular function has been described based on dot blot experiments. Fifty genes (25 regulators and 25 funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
2
6
0
1
Order By: Relevance
“…Cellular tolerance mechanisms during water deficit conditions are many and mainly include osmotic adjustment (Laszlo and Arnould, 2009), cell cycle control, protein chaperoning (Kovacs et al, 2008) and repair, removal of damaged proteins, production of scavenging enzymes and chromatin stabilization (Blum, 2005;Klutz, 2005). Diverse stress-responsive genes that regulate drought tolerance mechanisms have been shown to be upregulated when tissue water potential decreases (Bernacchia and Furini, 2004;Govind et al, 2009). Functional characterization of many of these stress-responsive genes has shown to sustain cellular metabolism under stress conditions (Amin et al, 2012;Amuda and Balasubramani, 2011;Dang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular tolerance mechanisms during water deficit conditions are many and mainly include osmotic adjustment (Laszlo and Arnould, 2009), cell cycle control, protein chaperoning (Kovacs et al, 2008) and repair, removal of damaged proteins, production of scavenging enzymes and chromatin stabilization (Blum, 2005;Klutz, 2005). Diverse stress-responsive genes that regulate drought tolerance mechanisms have been shown to be upregulated when tissue water potential decreases (Bernacchia and Furini, 2004;Govind et al, 2009). Functional characterization of many of these stress-responsive genes has shown to sustain cellular metabolism under stress conditions (Amin et al, 2012;Amuda and Balasubramani, 2011;Dang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…SOD is the front-line enzyme in ROS attack, since it rapidly scavenges superoxide, dismutating it to oxygen and H 2 O 2 which in turn activates downstream antioxidative enzymes there by scavenging ROS [6]. Although these physiological and biochemical mechanisms of stress response are common to all the plants, major differences exist in terms of strategies adapted by different crop species to cope with drought stress [7].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription was found only in runner genotypes, higher expression in endosperm (8x) and embryo of extra-large, rich in fatty acids and more tolerant to drought than IAC Caiapo (Santos et al, 2012a and b). Findings in the literature report transcriptional upregulation of DRM1/ARP family members in response to abiotic factors, such as drought and salt, in several species including A. hypogaea (Shimizu et al, 2006;Govind et al, 2009). Considering that both runner genotypes have expressive seed dormancy, it is possible that higher expression found in LGoPE-06 could be associated with expression of other traits, such as environmental adaptation.…”
Section: Relative Expression Of Nced Arp and Dmrmentioning
confidence: 99%
“…According to Rae et al (2013), besides the processes of dormancy, regulation of DRM1/ARP has been assessed in response to a number of treatments: hormonal, sugars, and abiotic and biotic across a number of plant species. In peanut, Govind et al (2009) reported DRM1/ARP transcript expression in response to gradual water stress. As BR 1 and L7 bege are earliness and widely tolerant to drought (Duarte et al, 2013), we suggest that higher expression found in endosperm of these materials could be benefited by effect of this trait.…”
Section: Relative Expression Of Nced Arp and Dmrmentioning
confidence: 99%